(subject reviewReview study ) Innovative artificial intelligence applications in the future of sports industry (Damu Journal of Sport Sciences, 2025)
Through this study, the researchers present a review of the most important recent research and studies in the field of artificial intelligence applications in the sports field. Today, we cannot imagine a sports industry without artificial intelligence.We will review the most important areas in which artificial intelligence is used in sports and how important it is, and we will review many examples and applications that have been tried in sporting events. An example of this isFIFA announced the goal-line technology (GLT) at the 2012 World Cup in Japan to help referees determine the goal. Tour De France previously collaborated with NTT Data Dimension to integrate machine learning, which enabled them to predict various events in cycling.Also The NBA is using technology at its best They were the first to launch a Facebook chatbot Live on social media The first game of the NBA Finals . These are just a few of the use cases where sports AI is preparing the world for revolution In this study we will explore innovative applications of how AI is revolutionizing the sports industry, improving the fan experience and the field of sports marketing.